Translanguaging in L3 Spanish Classrooms: Practices and Attitudes - Zhou, Xiaozhou (Emily); Huang, XiaoLing; He, Jili (Círculo de Lingüística Aplicada a la Comunicación, 2020)
Abstract. Research into pedagogical translanguaging in second/foreign language education has largely been focused on the interplay between two languages, one of which is usually English. Little attention has been paid to the practice of trilingual translanguaging (translanguaging between three languages), and how this can be helpful in the acquisition of a third language. This study, conducted in two Spanish as a third language classrooms in a Chinese university, aims to explore teachers’ translanguaging practices as well as the teachers’ and students’ attitudes to these practices. Analysis of data collected through audio-assisted classroom observation, interviews, and questionnaires reveals that teachers proactively and flexibly mobilize their multilingual resources in classroom talk. Students in general express positive attitudes towards teachers’ translanguaging practices, and express a wish to experience a greater amount of bilingual translanguaging between English (L2) and Spanish (L3). Meanwhile, having access to the views of L3 learners on teachers’ classroom talk proves to be a crucial component in the understanding of how L3 teaching and learning can take place in the most effective way. This study calls for further research into translanguaging practice in multilingual classrooms and its impact on students’ learning.
Keywords: translanguaging; L3 acquisition; Spanish; Spanish attitudes